2000
DOI: 10.1161/01.hyp.35.1.409
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Renin-Angiotensin System Modulates Angiotensin II–Induced Hypertension and Cardiac Hypertrophy

Abstract: Abstract-The potential involvement of the brain renin-angiotensin system in the hypertension induced by subpressor doses of angiotensin II was tested by the use of newly developed transgenic rats with permanent inhibition of brain angiotensinogen synthesis [TGR(ASrAOGEN)]. Basal systolic blood pressure monitored by telemetry was significantly lower in TGR(ASrAOGEN) than in Sprague-Dawley rats (parent strain) (122.5Ϯ1.5 versus 128.9Ϯ1.9 mm Hg, respectively; PϽ0.05). The increase in systolic blood pressure induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 28 publications
7
66
0
1
Order By: Relevance
“…Following on from this, in this study, we aimed to confirm the relevancy of Ang II-dependent central mechanisms for regulating HPA activity by using TGR(ASrAOGEN) that lacked brain Ang II (Schinke et al 1999). Consistent with many other studies, a slight hypotension was observed in the TGR(ASrAOGEN), which served as the fundamental characteristic of this transgenic rat in most of the studies (Baltatu et al 2000, Wang et al 2004, Campos et al 2006.…”
Section: Discussionsupporting
confidence: 54%
“…Following on from this, in this study, we aimed to confirm the relevancy of Ang II-dependent central mechanisms for regulating HPA activity by using TGR(ASrAOGEN) that lacked brain Ang II (Schinke et al 1999). Consistent with many other studies, a slight hypotension was observed in the TGR(ASrAOGEN), which served as the fundamental characteristic of this transgenic rat in most of the studies (Baltatu et al 2000, Wang et al 2004, Campos et al 2006.…”
Section: Discussionsupporting
confidence: 54%
“…Emerging evidence suggests that local formation is of major significance in the regulation of the Ang levels in many organs and tissues. For example, there is substantial evidence that the Ang peptide levels in the brain are regulated in an autonomous manner (Baltatu et al, 2000). Although every organ system in the body has elements of the RAS, the kidney is unique in having every component of the RAS with compartmentalization in the tubular and interstitial networks as well as intracellular accumulation.…”
Section: Mechanisms Responsible For Independent Regulation Of Intmentioning
confidence: 99%
“…Emerging evidence has demonstrated the importance of the tissue RAS in the brain (1), heart (7), adrenal glands (34), vasculature (5,13,15,36), and kidneys (37). The RAS has been acknowledged as an endocrine, paracrine, autocrine, and intracrine system and thus it has been difficult to delineate the quantitative contributions of systemically delivered vs. locally formed ANG peptides to the levels existing in any given tissue (37).…”
mentioning
confidence: 99%